Establishing a Secure Base to Increase Exploration of Diversity in Groups. Issue 2 (3rd April 2017) - Miles, Joseph R.; Mallinckrodt, Brent
ABSTRACT: All groups can be considered multicultural, and group members often present with issues that stem from contextual factors related to cultural identities, including experiences with oppression. Therefore, group leaders must be able to effectively facilitate deep intercultural dialogues in psychotherapy groups, and we suggest that an understanding of attachment theory can help leaders engage group members in these dialogues. In order to demonstrate how attachment theory can be applied to the exploration of diversity in groups, we provide a case example from an intergroup dialogue group bringing together religious minorities, secular individuals, and Christians over the course of eight weeks. In this example, we focus on the two group members who scored the lowest (Jill) and highest (Sarah) on a measure of attachment anxiety and avoidance to illustrate the experiences of one member with more secure attachment and one with more preoccupied attachment. Specifically, we present data from their weekly reflective journals to explore their different experiences of the group over time. Finally, we discuss the case in terms of attachment theory and highlight implications for group leaders.